(untitled) (Bangladesh Journal of Plant Taxonomy, 2023)
Verbascum globiferumHub.-Mor. and V. lysiosepalum Hub.-Mor.are endemic to Turkey which is a center of endemism for Verbascum species. This study gives the anatomical, palynological and seed micromorphological features of V. globiferum and V. lysiosepalumwhich grow in Diyarbakır.The xylem elements occupy a large area in the root cross-sections of the species. In stem cross-sections, the upper part of the epidermis cells is surrounded by a separate cuticle layer and the pith region covers a large area. In the leaves, the main vein is shapped as collateral bundle. Pollen grains are tricolporate-tricolpate, oblate-spheroidal, and exine ornamentation is reticulate. Seeds are brown and oblong-ovate to prismatic and alveolate. The seed coat ornamentation is irregular with polygonal cells, with densely, distinct vesicles.The capsules are pubescent, covered with stellate and branched hairy or glandular hairs.The seed displayed that substantial taxonomic understanding can be acquired from examining the seed characteristics of Verbascum, particularly at the species level. Bangladesh J. Plant Taxon. 30(2): 201-212, 2023 (December)